Application of a new spatial computable general equilibrium model for assessing strategic transport and land use development options in London and surrounding regions - Jie Zhu; Ying Jin; Marcial Echenique (European Regional Science Association (ERSA), 2012)
This paper reports the application of our new spatial computable general equilibrium (SCGE) model for analyzing the wider effects of strategic transport and land use development options. We examine the insights afforded by a SCGE model relative to those provided by existing land use and transport models into the effectiveness of transport and land use strategies. We start from a static imperfect competition computable general equilibrium model for an open economy, and extend it to incorporate (1) Hicks-neutral agglomeration effects that arise from external increasing returns to scale induced from urbanization and transport improvements, (2) land as an explicit factor input to production, and (3) commuting and migration of labour in a dynamic labour market. These extensions are built on models of constant elasticity of substitution specified for production technology and utility functions, interregional trade pooling, concave-shaped iceberg transport costs, the Armington specification regarding product varieties, the Dixit and Stiglitz type of monopolistic competition among producers, and the concept of the spatial economic mass. Data from London and surrounding regions is used to calibrate and validate the model. We report its applications in studying suburban road capacity expansion, high speed rail links and suburban and exurban land supply. The model results obtained so far are in line with theoretical expectations and provide new quantification of the costs and benefits that feed into the assessment of those strategies. Some on-going and further developments of the model include (1) All exogenous parameters for setting up the model are subject to further refinement from conducting sensitivity tests with respect to the magnitude of the model responses, (2) Flows between zones can in the future be mapped on to transport networks, e.g. through linking to a detailed transport model, and (3) the model may be extended with a recursive dynamic structure for policy analysis by incremental policy horizons.
Keywords: C68; F12; F16; F17; O18; R13; R42; 330; Computable general equilibrium; spatial modelling; increasing returns to scale; integrated land use and transport modelling